ANALISIS YURIDIS TERHADAP PERBUATA N MELAWAN HUKUM OLEH PEMERINTAH DALAM PENERBITAN KEBIJAKAN PERDAGANGAN YANG BERDAMPAK PADA KERUGIAN INVESTASI KORPORASI ( STUDI Putusan No. 3091 K/Pdt/2025) - Iren Margaretha Gurusinga; Rodiatun Adawiyah; Muhammad Arif Prasetyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the qualification of unlawful acts by the government in issuing trade policies that result in corporate investment losses, as well as to examine the form of government legal liability and the considerations of the Supreme Court in Decision Number 3091 K/Pdt/2025. This research is a normative legal study employing statutory and case approaches. The results indicate that investment losses arising from government policies cannot automatically be classified as unlawful acts unless all elements stipulated in Article 1365 of the Indonesian Civil Code are fulfilled. In the decision, the Supreme Court considered that government policy constitutes a legitimate exercise of authority in protecting the public interest, and therefore does not meet the elements of unlawfulness and fault. Consequently, the government cannot be held civilly liable in the form of compensation. This study also shows that investment losses resulting from government policies are part of policy risk that must be anticipated by investors. Thus, legal protection for investment is not absolute, but must be balanced with the government’s authority in carrying out its regulatory functions. This research is expected to contribute to the development of law related to investment protection and government accountability in public policy.